COMPARATIVE STUDY OF STUDENT ORIENTED METHOD AND LECTURE METHOD OF TEACHING AT SCHOOL LEVEL - Sher Ali Khan; Anwar Shamim; Sultan Saleem; Kifayat Ullah (International Journal of Contemporary Issues in Social Sciences, 2023)
The main objective of the study was to identify the best method of teaching between student’s oriented method and Lecture Method in Mathematics at school level. An experimental research study was conducted to check the efficiency of Self-directed Learning method. For this purpose, the pretest-posttest Equivalent Group Design was used in the study. All students studying in 8th class district Karak were considered the population of the study. GCMS Chokara was randomly selected as a sample of the study. Eighty students of 8th class of GCMS Chokara were given pre-test and then they were divided into two group’s i-e experimental and control groups. A posttest was administered after 6 weeks of the treatment period. The difference between the Scores of pre-test and posttest of both groups were calculated by applying t-test and analysis of variance. Obtained data was analyzed, interpreted in tabular form. It was concluded that student oriented method techniques was more effective as Lecture Method of Mathematics.